Action, Enaction, Inter(en)action - Schiavio, Andrea (Empirical Musicology Review, 2015)
Leman and Maes offer a comprehensive review of the main theoretical and empirical themes covered by the research on music and embodied cognition. Their article provides an insight into the work being carried at the Institute for Psychoacoustic and Electronic Music (IPEM) of Ghent University, Belgium - in which they work - and presents a theory of the main implications of embodiment for music perception. The present paper is divided into three parts. In the first one, I will explore the conceptual topography of embodied music cognition as maintained by the authors, to see whether the empirical research proposed fits the aims of this standpoint. In the second I will argue that while Leman and Maes are right to move towards a more dynamically implemented stance, the arguments used to justify this shift seem to be inconsistent with the framework they account for. In the third and final part of this commentary I will claim that if the authors wish to dedicate their work to develop a truly embodied, sensorimotor, and dynamic account to music cognition, they would need to abandon some of the assumptions defended in their work, searching for further empirical corroboration in the concrete dynamics of interactive, or participatory, musical sense-making.